ANALISIS KUALITAS KESEHATAN BAGI PESERTA PROGRAM JAMKESMAS DI PUSKESMAS BERGAS KABUPATEN SEMARANG - Dian Kusuma Hastin; Ida Hayu Dwimawanti; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
One of the tasks of government is to provide health services to the community , especially to the poor . To facilitate the poor to health services , the government through the Ministry of Health held a health care program for the poor that health insurance program for the poor masyarakt or more popular with the name JAMKESMAS . Health services using JAMKESMAS card can be obtained throughout the government -owned general hospitals and also in all health centers . The purpose of this study was to analyze the quality of health services provided by the health center to the patient Bergas JAMKESMAS Program participants. . This study used a descriptive research type , based on a qualitative approach using 10 dimensions of Parasuraman namely Reliability ( reliability ) , responsiveness ( responsiveness ) , Competence ( knowledge ) , Access , Courtesy ( politeness ) , Communication ( communication ) , Credibility ( credibility ) , security ( security ) , understandings the customer ( the ability to understand the customer ) , and Tangibles ( physical evidence ) . Informants in this study is Bergas officer at the health center as a health care provider and patient JAMKESMAS Program participants as recipients of health services . The data source of this research through in-depth interviews conducted by researchers to the informant ( Indepth Interview ) . The results showed that the quality of health care for participants in the Health Center Program Bergas JAMKESMAS there are two dimensions that meet the dimensions are the dimensions of Parasuraman Communication ( communication ) , and Credibility ( credibility ) and still not meet the dimensional ddelapan Parasuraman dimensions namely Reliability ( reliability ) , responsiveness ( responsiveness ) , Competence ( knowledge ) , Access , courtesy ( politeness ) , security ( security ) , understandings the customer ( the ability to understand the customer ) , and Tangibles ( physical evidence. )